Comparison of bolus and continuous infusion of esmolol on hemodynamic response to laryngoscopy, endotracheal intubation and sternotomy in coronary artery bypass graft - Efe,Esra Mercanooglu (2014)
BACKGROUND AND OBJECTIVE: The aim of this randomized, prospective and double blinded study is to investigate effects of different esmolol use on hemodynamic response of laryngoscopy, endotracheal intubation and sternotomy in coronary artery bypass graft surgery. METHODS: After approval of local ethics committee and patients' written informed consent, 45 patients were randomized into three groups equally. In Infusion Group; from 10 min before intubation up to 5th minute after sternotomy, 0.5 mg/kg/min esmolol infusion, in Bolus Group; 2 min before intubation and sternotomy 1.5 mg/kg esmolol IV bolus and in Control Group; %0.9 NaCl was administered. All demographic parameters were recorded. Heart rate and blood pressure were recorded before infusion up to anesthesia induction in every minute, during endotracheal intubation, every minute for 10 minutes after endotracheal intubation and before, during and after sternotomy at first and fifth minutes. RESULTS: While area under curve (AUC) (SAP × time) was being found more in Group B and C than Group I, AUC (SAP × T int and T st) and AUC (SAP × T2) was found more in Group B and C than Group I (p < 0.05). Moreover AUC (HR × T st) was found less in Group B than Group C but no significant difference was found between Group B and Group I. CONCLUSION: This study highlights that esmolol infusion is more effective than esmolol bolus administration on controlling systolic arterial pressure during endotracheal intubation and sternotomy in CABG surgery.